Two new biting midges of the subfamily Forcipomyiinae Lenz (Diptera: Ceratopogonidae) from China - Chen, Haiying; Liu, Yangqing; Yu, Yixin (Zootaxa, 2012)
Two new species of biting midges in the subfamily of Forcipomyiinae Lenz are described and illustrated based on male adults: Lasiohelea habros Liu, Chen & Yu, sp. nov.; Atrichopogon brenthus Liu & Yu, sp. nov..